Prognostic and Predictive Value of the American Joint Committee on Cancer Pathological Prognostic Staging System in Nodal Micrometastatic Breast Cancer - Shi, Jian; Lian, Chen-Lu; Chi, Feng; Zhou, Ping; Lei, Jian; Hua, Li; Wang, Jun; He, Zhen-Yu; Wu, San-Gang (Frontiers in Oncology, 2020)
Introduction: To investigate the prognostic and predictive effect of the American Joint Committee on Cancer (AJCC) 8th edition pathological prognostic staging system in patients with T1-2N1micM0 breast cancer who underwent mastectomy. Methods: Data from T1-2N1micM0 breast cancer patients who underwent mastectomy from 2010–2014 were obtained from the Surveillance, Epidemiology, and End Results program. The chi-square test, binomial logistics regression, receiver-operating characteristics curve, competing-risk regression model, Cox proportional hazards regression model, and proportional hazard assumption were used for statistical analyses. Results: We identified 4729 patients, including 1062 patients were received postmastectomy radiotherapy (PMRT). Stage change occurred in 88.2% of the patients, of which 84.4% were downstaged and 3.7% were upstaged. Patients with higher pathological prognostic stages were independently predicted to receive PMRT. The 5-year breast cancer-specific survival (BCSS) was 97.5%, 93.7%, 90.1%, 86.0%, and 73.5% in disease stages IA, IB, IIA, IIB, and IIIA, respectively, according to the 8th edition criteria (P < 0.001). The AJCC 8th edition demonstrated moderate discriminative ability, and it had a significantly better ability to predict the BCSS than the AJCC 7th edition criteria (P < 0.001). The multivariate prognostic analysis showed that the new pathological prognostic staging was an independent prognostic factor affecting the BCSS. The BCSS worsened with an increase in the stage. The PMRT did not affect the BCSS regardless of the pathological prognostic stage. Similar trends were found using the competing-risks regression model. Conclusions: The 8th AJCC breast cancer pathological prognostic staging system downstaged 84.4% of patients with T1-2N1micM0 disease and the survival outcome prediction with this staging system was more accurate than the AJCC 7th edition system. Our study does not support using the prognostic stage as a guideline to escalate of PMRT.